Xenobiotic Conjugation with Dicarboxylic Acids - Mitchell, Stephen C.; Steventon, Glyn B. (Current Drug Metabolism, 2018)
Background: Although it is believed widely that the various routes of xenobiotic metabolism are now all known and effectively understood, occasionally there emerges a metabolite that signals a novel biotransformation pathway, especially where the xenobiotic may in some way interact with the myriad processes of intermediary metabolism. There are a few reports in the literature where saturated short-chain dicarboxylic acids have been exploited as conjugating agents and these unusual xenobiotic metabolites subsequently excreted intact in the urine. Method: Initially suggested by unpublished observations bolstered by extensive experience of the authors and colleagues in the field of xenobiochemistry, this narrative review has been supplemented by a search of bibliographic databases and the subsequent scrutiny of numerous peer-reviewed research articles. The resultant sparse and widely dispersed information has been examined, analysed and presented in this review. Results: Xenobiotic conjugation with dicarboxylic acids has been demonstrated to occur within several domains of life; microorganisms, plants, invertebrates and mammals. However, considering the number of xenobiotic metabolism investigations that have been undertaken reports of such conjugations are exceedingly rare. Conclusion: Dicarboxylic acid condensation with xenobiotic molecules may occur at nitrogen centres, or more precisely with a primary or secondary amine, that is at nitrogen still possessing a replaceable hydrogen atom. Both aliphatic amines and arylamines may be substrates with many of the free amino groups being formed by previous Ndealkylation reactions. Hopefully, awareness of this metabolic route will be raised and researchers will be enthused to search for this type of conjugate.
Keywords: Dicarboxylic acids